Intrinsic and Extrinsic Factors Related to the Incident of Toddler Pneumonia - Jannah, Miftahul; Abdullah, Asnawi; Hidayat, Melania; Asrar, Qatratul (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
According to the Regional Task Unit of Banda Raya Public Health Service, Banda Aceh City, there was an increase in Pneumonia Toddlers from 62 patients in 2017 to 135 patients in 2018. This study aims to determine the intrinsic and extrinsic risk factors related to the incidence of toddlers pneumonia in the work area of the Regional Task Unit of Banda Raya Public Health Service, Banda Aceh City, in 2019. Spatial analysis was used to analyze and describe the results of toddler pneumonia distribution and to see the relationship between intrinsic and extrinsic factors to the incidence of toddlers pneumonia using a Case-Control Study or Retrospective Study design. This study uses a total population sample of 142 people, consisting of 71 cases and 71 controls using a 1:1 ratio. The results showed that the variables associated with pneumonia were education (OR=2.47; 95% CI=1.51-5.32; p value=0.049), vitamin A administration (OR=4.56; 95% CI=1.81-11.49; p value=0.001), and exclusive breastfeeding (OR=0.35; 95% CI=0.11- 1.09; p value=0.072). Intrinsic factors related to the incidence of pneumonia are vitamin A administration and exclusive breastfeeding. Then the Extrinsic factor related is education. The recommendation is to improve MCH management, such as complete basic immunization, vitamin A administration, and others.